Evaluating the Effect of Financial Penalty on Hospital-Acquired Infections - Wood DM; Beauvais B; Sturdivant RX; Kim FS (Dove Medical Press, 2024)
Dan M Wood,1,* Brad Beauvais,2,* Rodney X Sturdivant,3,* Forest S Kim4,* 1Graduate Program in Health and Business Administration, Army-Baylor University, San Antonio, TX, USA; 2School of Health Administration, Texas State University, San Marcos, TX, USA; 3Department of Statistical Science, Baylor University, Waco, TX, USA; 4Department of Economics, Baylor University, Waco, TX, USA*These authors contributed equally to this workCorrespondence: Dan M Wood, Army-Baylor University MHA/MBA Program, 3630 Stanley Road, San Antonio, TX, 78234, USA, Email dan_wood@baylor.eduPurpose: This study explores the effects of CMS reimbursement financial penalties from the Hospital-Acquired Condition Reduction Program (HACRP) on hospital-acquired infections (HAI) in hospitals across the United States.Methods: Hospital-level data for 2896 hospitals in the United States were evaluated using multiple linear regression models with random effects analysis through a difference-in-differences study design to examine HAIs under the HACRP between hospitals that were financially penalized or not from calendar years 2013 to 2020.Results: This study showed significant differences from the pre-program Total HAC scores to the most recent reviewed year, validating the efficacy of the HACRP, and showing a reduction of overall HAIs over the years evaluated in the study. The multiple linear regression model with random effects analysis produced a significant (p < 0.001) interaction term between hospitals expected to be penalized in 2013 and each year evaluated in the study (− 0.412 estimate) confirming decreases in HAI scores, and overall decreases in HAIs across the years of the study. Notably, 98% of hospitals in the worst-performing, expected to be financially penalized quartile from 2013, were found to have decreased their HAIs in their facilities, while only 38.8% of hospital in the performing, non-penalized quartiles showed decreases in HAIs across their facilities, by 2020.Conclusion: Our research indicates that implementing financial disincentives through reimbursement reductions could potentially decrease the incidence of HAIs. Our study further suggests that incorporating financial penalties and incentives for HAIs annually across all hospitals may lead to significant reductions in HAIs throughout the US healthcare system.Keywords: HACRP, medicare, reimbursements, CMS PSI-90 scores